2021
DOI: 10.3892/ol.2021.12910
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑133a‑3p inhibits cell proliferation, migration and invasion in colorectal cancer by targeting AQP1

Abstract: Recently, miR-133a-3p has been identified as a marker for human colorectal cancer (CRC) and the association between miR-133a-3p and aquaporin 1 (AQP1) has been described in endothelial cells. However, the regulatory functions of the miR-133a-3p/AQP1 axis remain unclear in CRC. The present study analyzed the expression of miR-133a-3p and AQP1 in CRC tissues (n=56) and cell lines using reverse transcription-quantitative PCR and western blot analysis. The χ 2 test was used to assess the associations between miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Inhibition of miR-430-3p also rescued the effects of circ_0001789 silencing. These data were consistent with previous findings that miR-140-3p served as a tumor suppressor to inhibit the metastasis of various cancer types [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Inhibition of miR-430-3p also rescued the effects of circ_0001789 silencing. These data were consistent with previous findings that miR-140-3p served as a tumor suppressor to inhibit the metastasis of various cancer types [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to circRNAs, microRNAs (miRNAs or miRs) are another class of short non-coding RNAs that are involved in the progression of GC [ 11 , 12 ]. For example, miR-140-3p has been reported as a tumor suppressor that inhibits the metastasis of various types of cancer [ 13 , 14 ]. miR-140-3p could also promote autophagy, and alleviate inflammatory and oxidative stress to mitigate cell damage [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[40] An additional study found that miR-140-3p was downregulated in NSCLC tumours; compared with adjacent normal lung tissue. [41] In addition, miR-29c-3p also showed the potential of using it as a non-invasive blood-based biomarker for the detection of NSCLC. Studies demonstrated that miR-29c-3p suppresses colon cancer cell growth and suppresses hepatocellular carcinoma tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Aquaporin 1 (AQP1) was signi cantly associated with prognosis in patients with lung cancer. Kong et al found that MicroRNA-133a-3p inhibits cell proliferation, migration and invasion in colorectal cancer by targeting AQP1 [13]. Angelico et al found that Aquaporin-1 (AQP1) is highly expressed in asbestos-related malignant pleural mesothelioma (MPM) [14].…”
Section: Discussionmentioning
confidence: 99%